Surgical Management of Crohn Disease in Children: Guidelines From the Paediatric IBD Porto Group of ESPGHAN - Amil-Dias, Jorge; Kolacek, Sanja; Turner, Dan; Pærregaard, Anders; Rintala, Risto; Afzal, Nadeem A; Karolewska-Bochenek, Katarzyna; Bronsky, Jiri; Chong, Sonny; Fell, John; Hojsak, Iva; Hugot, Jean-Pierre; et al. (Journal of pediatric gastroenterology and nutrition, 2017)
The incidence of Crohn disease (CD) has been increasing and surgery needs to be contemplated in a substantial number of cases. The relevant advent of biological treatment has changed but not eliminated the need for surgery in many patients. Despite previous publications on the indications for surgery in CD, there was a need for a comprehensive review of existing evidence on the role of elective surgery and options in pediatric patients affected with CD. We present an expert opinion and critical review of the literature to provide evidence-based guidance to manage these patients. Indications, surgical options, risk factors, and medications in pre- and perioperative period are reviewed in the light of available evidence. Risks and benefits of surgical options are addressed. An algorithm is proposed for the management of postsurgery monitoring, timing for follow-up endoscopy, and treatment options.
Keywords: Immunosuppressive Agents; biologická terapie; Colectomy; antiflogistika; Intestine, Small; lidé; kolektomie; tenké střevo; Crohnova nemoc; Elective Surgical Procedures; Patient Selection; elektivní chirurgické výkony; Perioperative Care; recidiva; Biological Therapy; Postoperative Complications; Secondary Prevention; perioperační péče; dítě; výběr pacientů; Child; Anastomosis, Surgical; imunosupresiva; Anti-Inflammatory Agents; Humans; Recurrence; anastomóza chirurgická; Crohn Disease; adjuvantní chemoterapie; Chemotherapy, Adjuvant; pooperační komplikace; sekundární prevence